Analisis Perbandingan Routing Protocol Open Shortest Path First dan Enhanced Interior Gateway Routing Protocol pada IPV6 menggunakan Graphical Network Simulator 3 - Pramita, Made Dinda Pradnya; Jasa, Lie (Majalah Ilmiah Teknologi Elektro, 2019)
Along with technological developments, implementing network computers can use network simulators. The use of network simulators that are often used, one of which is the Graphical User Interface (GUI) and the operating system provided by the user because the operating system used comes from the original operating system of the network device. Rapid development of data needs encourages people to exchange information with one another through one network. Data communication is done through sending data packets between networks based on internet protocol (IP) addresses. IP is divided into two, namely IPV4 and IPV6 in the process of sending data assisted by a router. In this study, the analyst will focus on routing protocol performance using IPV6 by paying attention to several parameters such as delay, packet loss, throughput and conversion time. Based on the results of the study, OSPF is better than EIGRP in the value of delay and throughput, which is 2- 15%. EIGRP is better when the connection is down, which is 45 - 52%. EIGRP has a faster convergence time than OSPF which is 2 - 6 seconds while OSPF is 8-10 seconds.